Changes on the antioxidant activity and total phenolics content of different leafy and fruit vegetables as affected by storage time and temperature - Hurtada, Wilma A. (Transactions of the National Academy of Science and Technology, 2011)
Antioxidants are known to provide health benefits such as the prevention of disease like cancer, cardio and cerebro vascular diseases. Vegetables contain considerable amount of antioxidant activity and total phenolic content of malunggay, pechay, chilli leaves, sweet potato tops, and kangkong and fruit vegetables okra, tomato, eggplant, ampalaya, sitao as they affected by storage temperatures and time of storage. Ten leafy and fruit vegetables were stored under cold and room temperatures and monitored for total phenolic content using the Folin-Ciocalteu method and antioxidative activity using the DPPH method until the end of marketability. Results were statistically analyzed. The antioxidative activity of leafy vegetables stored both at room temperature and refrigerated temperatures showed that prolonged and cold storage decreased. The total phenolics content of leafy vegetables stored at refrigerated temperature showed varied effects with chilli and malunggay decreased, while kangkong, sweet potato tops, and pechay increased. Generally, leafy vegetables stored at room temperature showed increasing trends while fruit vegetables exhibited decreasing total phenolics content except for okra and sitao. Storage time and temperature affect the antioxidant activity and total phenolic content of leafy and fruit vegetables. The total phenolics content of vegetables at room temperature increased while those at refrigerated temperature decreased. Antioxidative activity behaves otherwise.